STRATEGI GURU DALAM MENGEMBANGKAN KARAKTER DISIPLIN ANAK USIA DINI DI SATUAN PAUD SEJENIS KAWASEN - Hidayat, Yusuf; Kuncoro, Agus; Tunajijah, Ulfah; Muhimah, Lulu; Susiyani, N. Neni (Jurnal Intisabi, 2025)
Early childhood discipline is the obedience character possessed by early childhood to apply rules or norms. The present study aims to find out the teachers’ strategy and the realization of the implementation of the teachers’ strategy to develop early childhood’s discipline in early childhood education in Kawasen, Banjarsari, Ciamis. This study uses a qualitative method under the Phenomenological approach. The results of the study show that there are two strategies carried out by the teachers: habituation and giving rewards strategies. The habituation strategy is carried out by the teachers, such as: the teachers motivate the early childhood; the teachers guide the early childhood by directing and inviting to behave disciplinedly; the teachers provide an understanding to do discipline; and the teachers instill the values of discipline character to the early childhood. Then, the giving rewards strategy is carried out by the teachers, such as: the teachers give star stickers; the teachers give praise to the early childhood who behave discipline; the teachers invite highs, so that the early childhood feel happy when they behave discipline.